Scientific Conference “Understandig Demographic Change” - Gołata, Elżbieta; Kotowska, Irena E. (Studia Demograficzne, 2025)
The “Understanding Demographic Change” conference,1 organised in Warsaw by the Committee on Demographic Studies of the Polish Academy of Sciences on June 13–14 as part of the Third Demographic Congress 2022, brought together leading researchers working on population issues in Poland and Europe. Its programme focused on the main problems addressed in research on population processes. The presentations and discussions in the individual sessions constitute an important contribution to the knowledge about the ongoing demographic change in Poland and in Europe, its determinants, and its consequences. This knowledge is essential for understanding demographic transformations both in European countries and in other regions of the world. This conviction led the Scientific Committee of the conference to developing a message containing the most important findings and conclusions of this important event.